Akathisia and restless legs - Sachdev, Perminder (Cambridge University Press, 1995)
This book reviews our knowledge of akathisia and related syndromes, including Restless Legs Syndrome, other forms of motor restlessness and neuroleptic-induced dysphoria and is a comprehensive account of these important, but insufficiently researched, syndromes. The main focus is on drug-induced akathisia and its various subtypes. The author explores its relationship to the restlessness caused by other neurological disorders, presents a synthesis of the pathophysiological mechanisms of akathisia and provides arguments for operational criteria for the research diagnosis of drug-induced akathisia. Strategies for the measurement of akathisia are discussed, as are treatment approaches and a fascinating appendix contains a translation of Hashovec's account of the first cases in the literature. As the first extended review of scientific and clinical aspects of akathisia and restlessness, this book will be much valued by psychiatrists, neurologists and other physicians seeking a better understanding of these disabling syndromes
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Tardive dyskinesia; Restless legs syndrome; Dyskinesie; Einführung